2018
DOI: 10.1002/2017ja025041
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of Spatial Variation of Relativistic Electron Precipitation Energy Spectra With Polar Operational Environmental Satellites

Abstract: The mechanisms that drive relativistic electron precipitation (REP) from the radiation belts can be better understood with a better knowledge of the particle energies involved. National Oceanic and Atmospheric Administration Polar Operational Environmental Satellites, being a network of multiple satellites, can provide multiple point spectral data over a long time period, including the Van Allen Probe's era. The number of energy channels is limited, but the particle detectors on Polar Operational Environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…During the time intervals of the presented case studies, the observed trapped electron flux at higher energies ( E > 2.6 MeV) that could be most effectively scattered by EMIC waves was distributed in a single belt and peaked at lower L values well inside the plasmasphere (Goldstein et al, ); thus, no detectable REP occurred at the 3:00 UT time period. The results of this case study are consistent with a recent statistical study by Shekhar et al (), which investigated electron precipitation observed by POES satellites and analyzed event hardness based on precipitation flux ratios. This study showed that a subset of precipitation that appeared to be energy selective had a shift in distribution of events with the highest‐energy events found at lower L values and earlier local times across the dayside magnetosphere and the lower energy events peaked closer to midnight at higher L values.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…During the time intervals of the presented case studies, the observed trapped electron flux at higher energies ( E > 2.6 MeV) that could be most effectively scattered by EMIC waves was distributed in a single belt and peaked at lower L values well inside the plasmasphere (Goldstein et al, ); thus, no detectable REP occurred at the 3:00 UT time period. The results of this case study are consistent with a recent statistical study by Shekhar et al (), which investigated electron precipitation observed by POES satellites and analyzed event hardness based on precipitation flux ratios. This study showed that a subset of precipitation that appeared to be energy selective had a shift in distribution of events with the highest‐energy events found at lower L values and earlier local times across the dayside magnetosphere and the lower energy events peaked closer to midnight at higher L values.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, other scattering mechanisms could explain such outliers. Statistical studies from Smith et al () and Shekhar et al () suggest current sheet scattering as a possible precipitation mechanism that occurs in a region that can overlap with the region of EMIC wave‐driven precipitation. Further work is required to utilize complementary satellite observations such as POES, GOES, and Van Allen Probes to look for EMIC waves associated with the REP observed by balloons and coincident proton precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…All the cases occurred during substorms, within the plasmasphere (at least during the periods when RBSP density measurements were available) and near the dusk sector, in agreement with previous studies (Shekhar et al, ; Yahnin et al, ), given the favorable region of EMIC wave excitation due to ring current proton injections (Jordanova et al, ). The precipitation trends at low orbit all show strong precipitation of both ring current protons and relativistic electrons (E4 channel onboard POES/MetOp), with precipitation patterns very similar across all the available LEO satellites located near the conjugate locations of the EMIC wave activity observed by RBSP.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…Since both protons and electrons can interact with EMIC waves via cyclotron resonance, typical signatures of EMIC‐driven precipitation show simultaneous precipitation of tens of keV protons and relativistic electrons (Carson et al, ). Statistical studies reveal that such events occur mainly in the afternoon‐midnight sector (Shekhar et al, ; Yahnin et al, ), in agreement with the favorable location of EMIC wave enhancements in association with ring current injections (Morley et al, ; Pickett et al, ; Usanova et al, ). A recent study by Hirai et al () showed direct evidence of correlation between the rising tone EMIC wave structure and the associated bursts of REP.…”
Section: Introductionmentioning
confidence: 55%
“…Other case studies have also demonstrated a connection between precipitation events and EMIC waves (Blum et al, ; Clilverd et al, ; Clilverd et al, ; Hendry et al, ; Hendry et al, ; Rodger et al, ). It is possible that other mechanisms might be responsible for some of the Hendry et al () events (see, e.g., Shekhar et al, ; Smith et al, ; Yahnin et al, ). But it seems that many of these events probably are caused by EMIC waves.…”
Section: Discussionmentioning
confidence: 99%